Therapeutic Challenges in Systemic Lupus Erythematosus Patient with Pregnancy, Osteoporosis, and Severe Thrombocytopenia: A Case Report and Review of Literature - Ratnaningtyas, Yosefin; Rahman, Perdana Aditya (Jurnal Kedokteran Brawijaya, 2021)
Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease that requires long-term corticosteroid treatment that may lead to osteoporosis characterized by low bone mass and microarchitectural deterioration of the trabecular and cortical skeletal. This study presents a severe case of thrombocytopenia in a 25-year old woman with SLE and osteoporosis who underwent routine therapy and was pregnant for the first time. The complexity of pregnancy and autoimmune conditions create therapeutic challenges that need to be considered in SLE patients with pregnancy, osteoporosis, and severe thrombocytopenia.